Effect of vitamin E-coated dialysis membranes on anemia in patients with chronic kidney disease: an Italian multicenter study - Cruz, D N; De Cal, M; Garzotto, F; Brendolan, A; Nalesso, D; Corradi, V; Ronco, C (International journal of artificial organs, 2008)
Increased oxidant stress is increasingly recognized as a crucial factor in anemia in patients with chronic kidney disease. Vitamin E-coated membranes (VECMs) consist of a multilayer membrane with liposoluble vitamin E on the blood surface allowing direct free radical scavenging at the membrane site, which is of potential clinical benefit. Our objective was to examine the effect of VECMs on anemia in chronic hemodialysis (HD). We enrolled 172 stable chronic HD patients (94 men, 78 women, age 65.4 +/- 13.4 years) in an open-label multicenter study. They were shifted from their previous dialyzer to VECM for 1 year. Hemoglobin (Hb) levels and recombinant human erythropoietin (rHuEpo) dosage were analyzed after 4, 8, and 12 months on the VECM and compared with baseline values using paired tests. Hb significantly increased from 10.9 +/- 1.2 g/dL at baseline to 11.7 +/- 1.2 g/dL after 12 months (p<0.001) on VECMs. Conversely, the rHuEpo dosage decreased from 7,762 +/- 5,865 IU/week at baseline to 6,390 +/- 5,679 IU/week after 12 months (p<0.001). The proportion of patients who were at target Hb levels (European Best Practice Guidelines) increased from 49.4% at baseline to 80% after 12 months (p<0.001). Dialysis with VECM in stable chronic HD patients was associated with significantly improved Hb levels and lower rHuEpo requirements. These results suggest that the antioxidant properties of VECMs may impact favorably on anemia management in chronic HD patients. Possible mechanisms include enhanced membrane biocompatibility, reduced oxidative stress and inflammation with VECMs, resulting in improved red blood cell survival and/or rHuEpo responsiveness. This therapy may potentially contribute to more effective anemia management in hemodialysis patients, and merits further rigorous study.